The COVID-19 Consequence within the Framework of the Theory of Force Majeure & Emergency Circumstances - Rebaz Ardalan Bakr; Ranj Rasool Hamad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
First of all, the Contractual obligations are affected by the general circumstances surrounding the contract, such as the circumstances caused by the Covid-19, when the entire contract is paralyzed, and the implementation of contractual obligations is impossible, then we are in a force majeure situation, including what happened in the time of Covid-19, and if we are in front of Exhaustion afflicts one of the contracting parties, threatening him with a serious loss, as we are facing an emergency circumstance, and two assumptions, both of which are dealt with in accordance with the legal provisions adopted by the legislator in express legal texts. Therefore, this study was based on a problem centered on defining the exact legal description of COVID-19, in an attempt to reach the application of legal provisions appropriate to the existing legal situation, consistent with the requirements of achieving justice and the proper implementation of contracts, in order to ensure the stability of transactions and good application of the law. This is done through two sections. In the first section, we dealt with the consequences of Covid-19 in the framework of force majeure, and in the second section, we dealt with Covid-19 in the context of emergency circumstances.